2007
DOI: 10.1080/17493460701800207
|View full text |Cite
|
Sign up to set email alerts
|

Show and Tell: Accessing and Communicating Implicit Knowledge Through Artefacts

Abstract: This paper contributes to the current discourse on the role of artefacts in facilitating and triggering interaction among people. The discussion will focus on artefacts used as part of an interview method developed in order to discover knowledge that was observed but absent from both project reports and other documentation within multidisciplinary collaborative research projects, located within the field of Interaction Design. Using artefacts in an interview context enabled participants to reveal insights that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In the case described by Boer (2011) a provotype was designed in the shape of a lamp and five boxes to make people experience and relate to, in new ways, the concept of indoor climate. Yet another example can be found in the playful triggers, used by (Akama et al, 2007;Rettig, 2007) that support both collaboration and create meaningful dialogue.…”
Section: Explorative and Evaluative Prototypingmentioning
confidence: 99%
“…In the case described by Boer (2011) a provotype was designed in the shape of a lamp and five boxes to make people experience and relate to, in new ways, the concept of indoor climate. Yet another example can be found in the playful triggers, used by (Akama et al, 2007;Rettig, 2007) that support both collaboration and create meaningful dialogue.…”
Section: Explorative and Evaluative Prototypingmentioning
confidence: 99%
“…It is a tool associated with means of inspiring participant communication, built on the work of Loi (2005), Gaver et al (1999) and Sanders (2002). It uses commonly found, playful, everyday objects to access, interpret, visualise, articulate and communicate implicit knowledge through facilitated conversations (Akama 2007). The residents were shown an example of use undertaken earlier by a household in the local area.…”
Section: In the Eventmentioning
confidence: 99%
“…They were artefacts called Playful Triggers (Akama et al, 2007;Loi 2005). Figure 4 shows a close up of the objects that make up the Playful Triggers.…”
Section: Playful Triggers To Visualise 'Community Of Place'mentioning
confidence: 99%
“…Figure 4 shows a close up of the objects that make up the Playful Triggers. Playful Triggers are ethnomethodological tools, building on the work by Loi (2005), Gaver et al (1999), and Sanders (2000), where commonly found objects are used to access, interpret, visualise, articulate and communicate implicit knowledge through facilitated conversations (Akama et al, 2007). This methodology utilises playful, tactile, everyday qualities of objects.…”
Section: Playful Triggers To Visualise 'Community Of Place'mentioning
confidence: 99%
See 1 more Smart Citation